Implementation of Communication Information Technology in Distance Learning At Islamic Elementary School Insan Rabbani Tembilahan - Nur Azima; Martina Napratilora; Mardiah Mardiah; Dina Liana; Hendro Lisa (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2023)
This research was conducted to find out how educators implement communication information technology in distance teaching and what factors influence it at the Insan Rabbani Tembilahan Integrated Islamic Elementary School. This research s a qualitative study. There were 3 teachers in the Integrated Islamic Elementary School Insan Rabbani Tembilahan as respondents. The sampling technique uses a purposive technique. This data was obtained through observation, interviews, and documentation. The results of the study show that the implementation of information and communication technology by teachers in distance learning at the Integrated Islamic Elementary School Insan Rabbani Tembilahan is categorized as good with a percentage of sixty percent and located in intervals of sixty-one percent to eighty percent. Factors that influence it are external factors (environment and society), and internal factors (teachers, students, and technology).